Proposal for the revision of the guidelines for Non-clinical studies of vaccines for the prevention of infectious diseases in Japan. Issue 19 (26th April 2022) - Nomura, Yumiko; Noda, Kiyohito; Oohashi, Yuusuke; Okuda, Shin; Maki, Kazushige; Ogawa, Takashi; Nakano, Takashi; Tsuchida, Nao; Ishii, Ken J.; Hayashi, Kunihiko; Iiyama, Tatsuo; Onodera, Hiroshi; et al.
Highlights: We identified the current challenges in the development of vaccines and propose revision of the guidelines for the non-clinical studies of vaccines. The results of repeated-dose toxicity studies can be used to decide whether safety pharmacology studies are required. The studies to evaluate toxicity due to systemic effects may not be necessary for both intramuscular and subcutaneous administration. Women of childbearing potential could be included in clinical trials with appropriate pregnancy avoidance prior to the reproductive toxicity studies. Abstract: The efficacy and safety of vaccines for the prevention of infectious diseases are mostly evaluated based on the induction of an immune response against antigens, and do not necessarily depend on the dose administered. Therefore, there are some specific aspects that need to be considered in the development of vaccines and have been described in "The Guidelines for the non-clinical studies of vaccines for the prevention of infectious disease" in Japan. Recent changes in the vaccine development field, such as the introduction of vaccines developed overseas in Japan and vaccine development on a global scale have increased the need for revision of these guidelines. In this study, we identified the current challenges in the development of vaccines through comparison of Japanese and international guidelines. We conducted a questionnaire-based survey of pharmaceutical industries in Japan, and found issues related to non-clinical studies, such as the necessity of safety pharmacology studies and repeated-dose toxicity studies for each route of administration. We examined international guidelines on these issues as well as review reports by regulatory authorities, and determined that the results of repeated-dose toxicity studies can be used to decide whether safety pharmacology studies are required, and that studies to evaluate toxicity due to systemic effects may not be necessary for both intramuscular and subcutaneous administration. We propose revision of the guidelines for the non-clinical studies of vaccines in Japan taking international harmonizaion into account. We expected that the revised guidelines will promote smooth and rational vaccine development.